2005
DOI: 10.1007/s10549-005-1409-1
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer predisposing alleles in Poland

Abstract: Mutant alleles of several genes in the DNA repair pathway have been found to predispose women to breast cancer. From a public health perspective, the importance of a given allele in a population is determined by the frequency of the allele and by the relative risk of breast cancer that it confers. In Poland founder alleles of the BRCA1, CHEK2 and NBS1 genes have been associated with an increased risk of breast cancer, but the relative contribution of each of these alleles to the overall breast cancer burden ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 10 publications
(15 reference statements)
9
104
2
Order By: Relevance
“…After screening, we excluded articles in which CHEK2 I157T was not a studied variant or in which CHEK2 I157T was studied but not in breast cancer. 21 studies (Allinen et al, 2001;Schutte et al, 2003;Cybulski et al, 2004;Dufault et al, 2004;Kilpivaara et al, 2004;Bogdanova et al, 2005;Górski et al, 2005;Cybulski et al, 2006;Nevanlinna et al, 2006;Meyer et al, 2007;Cybulski et al, 2008;Falchetti et al, 2008;Novak et al, 2008;Kaufman et al, 2008;Kleib et al, 2008;Serrano-Fernandez et al, 2009;Scharrer et al, 2010;Cybulski et al, 2011;Domagala et al, 2011) examined the association between CHEK2 variants and breast cancer susceptibility. We then excluded non-casecontrolled, data duplicating, review, new gene variant, and male breast cancer studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening, we excluded articles in which CHEK2 I157T was not a studied variant or in which CHEK2 I157T was studied but not in breast cancer. 21 studies (Allinen et al, 2001;Schutte et al, 2003;Cybulski et al, 2004;Dufault et al, 2004;Kilpivaara et al, 2004;Bogdanova et al, 2005;Górski et al, 2005;Cybulski et al, 2006;Nevanlinna et al, 2006;Meyer et al, 2007;Cybulski et al, 2008;Falchetti et al, 2008;Novak et al, 2008;Kaufman et al, 2008;Kleib et al, 2008;Serrano-Fernandez et al, 2009;Scharrer et al, 2010;Cybulski et al, 2011;Domagala et al, 2011) examined the association between CHEK2 variants and breast cancer susceptibility. We then excluded non-casecontrolled, data duplicating, review, new gene variant, and male breast cancer studies.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, we identified thirteen studies of unselected breast cancer (Allinen et al, 2001;Schutte et al, 2003;Cybulski et al, 2004;Kilpivaara et al, 2004;Bogdanova et al, 2005;Górski et al, 2005;Huzarski et al, 2005;Cybulski et al, 2008;Kleib et al, 2008;Serrano-Fernandez et al, 2009;Scharrer Cybulski et al, 2011;Domagala et al, 2011) and three of lobular breast cancer Cybulski et al, 2011;Domagala et al, 2011). Characteristics of included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of published reports have suggested that mutations in NBS1, especially 657del5, is associated with elevated risk for some cancers, including ovarian (13), breast (7,8,10), melanoma (7,9), and lymphoid malignancies (7,11,12), such findings have not been replicated in other studies (21)(22)(23)(24). For prostate cancer, Cybulski et al (5) found that the 657del5 mutation was a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…nhgri.nih.gov/bic/). In several populations, the spectrum of mutations is rather limited, reflecting a single or a limited number of 'founder mutation(s)': the Dutch, 1 Icelandic, 2 the Polish, 3 Russian, 4 and the Norwegian 5 populations. Notably, among Ashkenazi Jews (ie, Jews of east European ancestry), three mutations in BRCA1 (185delAG, 5382InsC) and BRCA2 (6174delT) occur frequently.…”
Section: Introductionmentioning
confidence: 99%